Sputtered PdO Decorated TiO2 Sensing Layer for a Hydrogen Gas Sensor. (10th April 2018) - Lee, Jeong Hoon; Kwak, Seungmin; Lee, Jin-Hyung; Kim, Inho; Yoo, Yong Kyoung; Lee, Tae Hoon; Shim, Young-Seok; Kim, Jinseok; Lee, Kyu Hyoung
Abstract : We report a sputtered PdO decorated TiO2 sensing layer by radiofrequency (RF) sputtering methods and demonstrated gas sensing performance for H2 gas. We prepared sputtered anatase TiO2 sensing films with 200 nm thickness and deposited a Pd layer on top of the TiO2 films with a thickness ranging from 3 nm to 13 nm. Using an in situ TiO2 /Pd multilayer annealing process at 550°C for 1 hour, we observed that Pd turns into PdO by Auger electron spectroscopy (AES) depth profile and confirmed decorated PdO on TiO2 sensing layer from scanning electron microscope (SEM) and atomic-force microscope (AFM). We also observed a positive sensing signal for 3, 4.5, and 6.5 nm PdO decorated TiO2 sensor while we observed negative output signal for a 13.5 nm PdO decorated one. Using a microheater platform, we acquired fast response time as 11 sec and sensitivity as 6 μ V/ppm for 3 nm PdO under 33 mW power.